Hints towards the formation of a more comprehensive theory of life. - Coleridge, Samuel Taylor, 1772-1834 (Salt Lake City, UT : Project Gutenberg, 2008)
"Hints towards the formation of a more comprehensive theory of life" by Samuel Taylor Coleridge is a philosophical work published in 1818. Coleridge challenges Enlightenment science's mechanistic view of nature, seeking to understand life as more than mere matter in motion. Drawing on Romantic medicine and German natural philosophy, he proposes that life operates through dynamic polar forces$1 (Ba productive power that animates nature from within. This work bridges Romantic literature and science, arguing for a new paradigm that respects both material phenomena and the vital principles underlying existence. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Coleridge%27s_theory_of_life
Release date is 2008-01-17
Keywords: Life (Biology)